Biometric parameters of newborn drones of honeybee (Apis mellifera L.) and factors that affect them, in hives from Mayabeque, Cuba - Ocaña, Leyanis; Pérez, Anisley; Fernández, Ramara; Demedio, J. (Cuban Journal of Agricultural Science, 2021)
In order to determine biometric parameters of newborn drones of Apis mellifera L. and factors that affect them, a study was conducted in three apiaries from San José de las Lajas municipality, which included a monthly sampling of 10 hives/apiary, in November and December, 2015 and in January, 2016. An amount of 50 newborn individuals were examined, and their birth weight and body length were determined, as well as their fore right wing and body color. Infestation extension and intensity by Varroa destructor was evaluated. Weight and dimensions of drones were in correspondence with those of European breeds, and were influenced by the apiary of origin, sampling month and intensity of infestation. Key words: Apis mellifera, drones, biometrics, varroosis